THE IMPORTANCE OF TENURE AND ACCESS RIGHTS FOR INDIGENOUS PEOPLES - Hendra, Rahmad; Firmanda, Hengki; Samariadi, Samariadi; Manik, Rahmat GM. (Universitas Lampung, 2025)
This research was performed to develop a model of legal protection for tenure rights and Indigenous peoples' access to forests based on local and ecological wisdom in Riau Province. Socio-legal research methods are employed to examine the relationship between law and government policy, with a focus on local and ecological issues. This approach facilitates a more fundamental understanding of the law's substance. Using the normative analysis with interdisciplinary dialogue, in a protection model for public interests over the long term is proposed. The research suggests that cooperation between the public and local or regional governments can be pursued to implement a legal protection model for tenure rights, ensuring that the traditional rights of customary law communities are recognized and upheld within judicial processes. The protection of traditional and constitutional rights of customary law communities has not yet implemented in concrete actions. As a result, the private property rights and access to land in Riau Province are currently protected by the local and ecological considerations..